A biomechanical comparison of posterior malleolar fracture fixation using screws and locking plates in Trimalleolar fractures: a finite element study - Chih-Wei Chang; Yen-Nien Chen; Guan-Heng Jhong; Kuo-Chih Su; Chun-Ting Li (BMC Musculoskeletal Disorders)
Abstract Background The aim of the study is to compare the mechanical stability of posterior malleolar fractures fixed with different screw types and locking plates in the management of trimalleolar ankle fractures using the finite element (FE) method. Methods An FE model containing the distal tibia, fibula, talus, and calcaneus was created based on the computed tomographic images of a healthy man without any musculoskeletal disorders. The medial, lateral, and posterior malleoli were segmented using three virtual planes to create a trimalleolar fracture model, with the posterior malleolar fracture fragment comprising approximately 30% of the articular surface. Four different fixation approaches, including two partial thread cannulated screws (PTS), two full thread cannulated screws (FTS), and L-shaped (LLP) and T-shaped (TLP) locking plates with screws, were used to fix the posterior malleolar fracture. Two partial thread screws and a locking plate along with screws were used to fix the medial and lateral malleolar fractures, respectively. Two different loading conditions, namely static axial load and Achilles tendon force, were considered in the simulation. Results Under axial load, the maximum gap opening distance of the posterior malleolar fracture with screws only was obviously larger than that with locking plates. The maximum gap distance was 0.12 mm, 0.08 mm, 0.04 mm, and 0.05 mm in the PTS, FTS, LLP, and TLP, respectively. Under Achilles tendon force, the maximum gap opening distance were 0.12, 0.1, 0.03, and 0.1 mm, in the PTS, FTS, LLP, and TLP, respectively, under Achilles tendon force. Conclusion The results suggest that locking plates offer greater stability and reduce the fracture gap opening for posterior malleolar fractures involving 30% of the distal tibial articular surface in the fixation of trimalleolar ankle fractures.